Beneficial Effects of Probiotic Administration in Extremely Low Birthweight Infants: A Review - Beinlich, Steffi; V. Logomarsino, John (Journal of Nutritional Therapeutics, 2016)
The aim of this review was to evaluate the beneficial effects of probiotic supplementation on extremely low birthweight infants (birthweight <1000 g). Extremely low birthweight (ELBW) infants are the most vulnerable population in the neonatal intensive care unit (NICU). They are at the highest risk for necrotizing enterocolitis (NEC), sepsis, and inadequate nutrition due to their immature gastrointestinal (GI) function. Nutrition plays an important role in the future neurodevelopmental outcomes of these infants. Research methods for the review were conducted using PubMed and Cumulative Index to Nursing and Allied Health Literature (CINAHL). In total, eight research studies evaluated the effect of probiotic use in ELBW infants: three studies assessed GI colonization, five studies assessed enteral feeding and GI tolerance, one study assessed growth, five studies assessed NEC, five studies assessed sepsis, and two studies assessed length of hospital stay. This review found the use of probiotics improved GI tolerance, weight gain and length of hospital stay in ELBW infants, but was unable to make conclusions on the effect of probiotic use on incidences of NEC and sepsis. More research is needed in ELBW infants before making probiotic supplementation a standard of care in this population.